Study of A Class Of Multivalent Functions Defined By Dziak - Srivastava Operat With Application On Fractional Calculus (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the this paper we introduced  a class  of Multivalent  functions with negative coefficients defined by Dziak-Srivastava  operator and some application of Fractional Calculus , we obtain some theorems of this class. Mathematics subject classification:30C45.